Integrating the how and why of within-individual and among-individual variation and plasticity in behavior. (December 2015) - Alonzo, Suzanne H
Highlights: Understanding variation and plasticity is important for many questions about behavior. This may require the integration of evolutionary and mechanistic perspectives. The data required for this integration presents a conceptual and empirical challenge. We need concrete predictions about how mechanisms underlying plasticity evolve. This will require new theory and data that can inform and test this theory. Abstract : Although phenotypic variation within and among individuals in the same population may represent 'noise', it can also be the adaptive plasticity that allows organisms to adjust to varying environments or the heritable variation that fuels evolutionary change. Behavioral variation arises from a complex combination of adaptive and non-adaptive individual plasticity and consistency. Differentiating these sources of behavioral variation will require an integrated combination of evolutionary and mechanistic understanding. Yet, this integration comes with a variety of challenges. Here I argue that we will need concrete a priori predictions to make sense of the large and complex datasets this integration will require.